Single Dose of Attenuated Vaccinia Viruses Expressing H5 Hemagglutinin Affords Rapid and Long-Term Protection Against Lethal Infection with Highly Pathogenic Avian Influenza A H5N1 Virus in Mice and Monkeys - Fumihiko Yasui; Keisuke Munekata; Tomoko Fujiyuki; Takeshi Kuraishi; Kenzaburo Yamaji; Tomoko Honda; Sumiko Gomi; Misako Yoneda; Takahiro Sanada; Koji Ishii; Yoshihiro Sakoda; Hiroshi Kida; et al. (Vaccines)
Background/Objectives: In preparation for a potential pandemic caused by the H5N1 highly pathogenic avian influenza (HPAI) virus, pre-pandemic vaccines against several viral clades have been developed and stocked worldwide. Although these vaccines are well tolerated, their immunogenicity and cross-reactivity with viruses of different clades can be improved. Methods: To address this aspect, we generated recombinant influenza vaccines against H5-subtype viruses using two different strains of highly attenuated vaccinia virus (VACV) vectors. Results: rLC16m8-mcl2.2 hemagglutinin (HA) and rLC16m8-mcl2.3.4 HA consisted of a recombinant LC16m8 vector encoding the HA protein from clade 2.2 or clade 2.3.4 viruses (respectively); rDIs-mcl2.2 HA consisted of a recombinant DIs vector encoding the HA protein from clade 2.2. A single dose of rLC16m8-mcl2.2 HA showed rapid (1 week after vaccination) and long-term protection (20 months post-vaccination) in mice against the HPAI H5N1 virus. Moreover, cynomolgus macaques immunized with rLC16m8-mcl2.2 HA exhibited long-term protection when challenged with a heterologous clade of the HPAI H5N1 virus. Although the DIs strain is unable to grow in most mammalian cells, rDIs-mcl2.2 HA also showed rapid and long-lasting effects against HPAI H5N1 virus infection. Notably, the protective efficacy of rDIs-mcl2.2 HA was comparable to that of rLC16m8-mcl2.2 HA. Furthermore, these vaccines protected animals previously immunized with VACVs from a lethal challenge with the HPAI H5N1 virus. Conclusions: These results suggest that both rLC16m8-mcl2.2 HA and rDIs-mcl2.2 HA are effective in preventing HPAI H5N1 virus infection, and rDIs-mcl2.2 HA is a promising vaccine candidate against H5 HA-subtype viruses.